A Model Based Upon the Cross-Correlation Function Between the Potential and Wave Functions for Disordered Solids - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
A formulation for the cross-correlation function between the potential and Schrödinger wave functions with respect to the spacing between consecutive atoms in an infinite one-dimensional disordered solid is proposed. In this theoretical model, the argument of the above cross-correlation function is the spacing in question which is regarded as a random variable.